Dielectric and optical properties of B₂O₃ – TeO₂ – Sm₂O₃ glass system - Che Ab Rahman, Che Zuraini (2014)
Glasses containing ternary system (B2O3)30 (TeO2)70-x (Sm2O3)x and (B2O3)30-x (TeO2)70 (Sm2O3)x were prepared by melt-quenching technique over a wide range of composition (x = 0.3, 0.5, 0.7, 1.0 and 1.2 mol %) denoted as BTS1, BTS2, BTS3, BTS4, BTS5 and BTS6, BTS7, BTS8, BTS9, BTS10 respectively. The present study characterize Sm2O3 doped TeO2-B2O3 glasses composition, physical, structural, optical and dielectric properties as a function of frequency and temperature as well as the effect of the rare earth ions (Sm3+ ions) introduced into these glasses systems. The present investigation on the dielectric properties is useful to understand the basic mechanism of the polarization process, and the parameters necessary for the basic understanding of the physical grounds of optical properties. The structural changes were studied by X-Ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy and Differential Thermal Analysis (DTA) curve. All glasses studied in the present work exhibit amorphous materials. Network units existed in Sm3+ doped glasses and Sm3+ ions existed as network modifiers. The higher concentration of Sm3+, the more units of TeO3 groups transform to TeO4 groups in BTS1 - BTS5, more units deformed TeO4 group were transform to TeO3 groups in BTS6 - BTS10 and the transformation of some BO4 unit into BO3 units. The optimum Sm3+ concentration was about 1.0 mol% (BTS4 and BTS9) for this glasses system due to the Sm3+ concentration quenching. The density (ρ) decreases and molar volume (Vm) were reversed to ρ, attributed to non-bridging oxygen as the addition of samarium oxide (Sm) content. The addition of samarium oxide (4f5) indicates strong bonding between the components and enhances the glass formation ability (GFA). The optical and dielectric properties were studied in the frequency ranging from 10-2 Hz to 106 Hz, at temperature ranging from 373 K to 493 K. The dielectric properties (dielectric constant, ε’, and dielectric loss factor, ε’’) show a larger value at lower frequencies (below 100 Hz) and higher temperatures (above 413 K). The graphs were fitted using Cole-Cole functions and Quasi dc models. Activation energy obtained from the master curve graph was found to decrease as Sm2O3 content increased. The optical properties show that the indirect band gap values are decreasing with Sm2O3 content up to BTS4 (2.24 to 2.12 eV) and BTS9 (2.32 to 2.18 eV) attributed to increase in degree of disorder in the system, direct consequence of the increases of non-bridging oxygen in the system.